Response to Altmann: On the Need and Theory of Elementary Counseling - Chisan, J. B. (Canadian Journal of Counselling and Psychotherapy, 2012)
In his response to Altniann, the writer is critical of the abundance of quotations and assertions which lack logic and sense. The fact that some children in the elementary schools need assistance does not justify the need of counselors. Such an assumption may even be dangerous. A theory of elementary counseling, if it is to be anything more than a rambling statement, must take into account the lack of awareness, the immaturity, and the verbal and conceptual limitations of the child. If the two examples given by Altmann are the best to be found in the literature, probably a theory appropriate to children has yet to be proposed. It is sug- gested that the counselor not counsel but rather consult with the child and counsel the teachers and parents, bringing about modifications in the environment so that appropriate behavior is elicited. Outcome and spon- taneous remission studies tend to make counseling a highly questionable practice. NOTE: An abstract of the Altmann article follows: THE NEED, FUNCTION, AND THEORY OF ELEMENTARY COUNSELING ABSTRACT: A review of the literature on elementary counseling was made in an attempt to determine the status of this field. Specific issues involving need, function, and theory of elementary counseling were discussed. RESUME:On a effectué une revue de la littérature sur le counseling au veau primaire afin d'en établir le statut. On a ensuite discuté de certains problèmes spécifiques con